Assessing the status of the KNM-ER 42700 fossil using Homo erectus neurocranial development. Issue 154 (May 2021) - Baab, Karen L.; Nesbitt, Allison; Hublin, Jean-Jacques; Neubauer, Simon
Abstract: Based on ontogenetic data of endocranial shape, it has been proposed that a younger than previously assumed developmental status of the 1.5-Myr-old KNM-ER 42700 calvaria could explain why the calvaria of this fossil does not conform to the shape of other Homo erectus individuals. Here, we investigate (ecto)neurocranial ontogeny in H. erectus and assess the proposed juvenile status of this fossil using recent Homo sapiens, chimpanzees ( Pan troglodytes ), and Neanderthals ( Homo neanderthalensis ) to model and discuss changes in neurocranial shape from the juvenile to adult stages. We show that all four species share common patterns of developmental shape change resulting in a relatively lower cranial vault and expanded supraorbital torus at later developmental stages. This finding suggests that ectoneurocranial data from extant hominids can be used to model the ontogenetic trajectory for H. erectus, for which only one well-preserved very young individual is known. However, our study also reveals differences in the magnitudes and, to a lesser extent, directions of the species-specific trajectories that add to the overall shared pattern of neurocranial shape changes. We demonstrate that the very young H. erectus juvenile from Mojokerto together with subadult and adult H. erectus individuals cannot be accommodated within the pattern of the postnatal neurocranial trajectory for humans. Instead, the chimpanzee pattern might be a better 'fit' for H. erectus despite their more distant phylogenetic relatedness. The data are also compatible with an ontogenetic shape trajectory that is in some regards intermediate between that of recent H. sapiens and chimpanzees, implying a unique trajectory for H. erectus that combines elements of both extant species. Based on this new knowledge, neurocranial shape supports the assessment that KNM-ER 42700 is a young juvenile H. erectus if H. erectus followed an ontogenetic shape trajectory that was more similar to chimpanzees than humans. Highlights: Vault shape in hominids develops with some shared and some species-specific aspects. Homo erectus vault development is more similar to the chimpanzee than human pattern. Assuming a chimp-like development, KNM-ER 42700 could be a juvenile H. erectus .